Application of Restorative Justice in Handling Account Transfer Errors by Banking Officials - Padlilah Padlilah; Heri Heriyanto (The Easta Journal Law and Human Rights, 2026)
Wrongful account transfers by bank officials are a problem that has a direct impact on customer confidence and the stability of the banking system, so it requires a settlement mechanism that is not only sanctions oriented, but also recovery. Although the restorative justice approach has begun to be introduced in the Indonesian legal system, its application in the context of banking administrative errors is still limited and has not been comprehensively studied. This study aims to analyze the application of restorative justice in handling account transfer errors by bank officials and assess its effectiveness in providing justice for the parties. The research method used is normative juridical with a legislative approach and conceptual studies, supported by related case analysis. The results of the study show that restorative justice can be an effective alternative settlement by emphasizing the recovery of customer losses, the responsibility of the perpetrator, and maintaining the reputation of the banking institution, if there is no element of intentionality or serious crime. The implication is that it is necessary to strengthen regulations and guidelines for the implementation of restorative justice in the banking sector to ensure legal certainty and customer protection.